Digitalization Of Funding Officers In Providing On-Shift Services To Customers Using The Collector Application - Jafar Shiddiq; Rama Sultan Duta Alamsyah (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2026)
The rapid development of digital technology has driven financial institutions, including Islamic rural banks, to transform their work systems in order to improve operational efficiency and service quality. PT BPR Syariah Lantabur Tebuireng, as a pesantren-based financial institution, has also embraced innovation by digitalizing the role of funding officers, particularly in the context of proactive customer outreach services. This study aims to describe the implementation of funding officer digitalization through the use of the Collector application in supporting field-based fundraising activities. A qualitative descriptive approach was used, with data collected through semi-structured interviews, field observations, and internal documentation. The findings reveal that the Kolektor application facilitates funding officers in digitally recording visit data, accessing real-time customer information, and submitting reports to management more quickly and accurately. This digitalization not only improves work efficiency but also strengthens personal relationships with customers through more responsive service. Additionally, the application enhances transparency, performance monitoring, and strategic planning by management. The results of this study indicate that digitalizing the role of funding officers can significantly enhance the competitiveness of Islamic rural banks in the digital era, while still upholding the values of Sharia and trust-based financial service principles.